2000
DOI: 10.1086/315454
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Dependent Neutralizing Humoral Response toSchistosoma mansoni28GST Antigen in Infected Human Populations

Abstract: The reduction of Schistosoma fecundity observed after experimental vaccination with the Schistosoma mansoni 28-kDa glutathione S-transferase (Sm28GST) antigen has been related to the inhibition of glutathione S-transferase (GST) enzymatic activity by specific antibody. The humoral immune response to the protective antigen Sm28GST and to the epitopes involved in the enzymatic site (amino acid ¿aa sequences 10-43 and 190-211) was evaluated in infected individuals before chemotherapy treatment. The capacity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…1,2 However, the intensity of infection may also be related to behavioral routines (water contact), 3,4 age, 5 and sex. 6,7 Individual susceptibility that is associated with the immunologic 8,9 and genetic profiles [10][11][12] of each individual living in the endemic area is also important.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, the intensity of infection may also be related to behavioral routines (water contact), 3,4 age, 5 and sex. 6,7 Individual susceptibility that is associated with the immunologic 8,9 and genetic profiles [10][11][12] of each individual living in the endemic area is also important.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the type of antibody response elicited after immunization with phagedisplayed Sm28GST is comparable to that elicited after a DNA vaccination with Sm28GST-encoding DNA, which is known to confer significant protection (12). Similarly, a recent study in northern Senegal showed that a low level of S. mansoni infection in the male population correlated with a high level of neutralizing IgG3 antibody against Sm28GST in their sera (22). Although we did not check whether the IgG3 antibody elicited by phage-displayed Sm28GST in male mice is a neutralizing antibody, the response seems to be comparable to those in humans.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, we have previously demonstrated during human schistosomiasis that immune response to 28GST was gender dependent, with a specificity of epitope recognition (22,23). The binding of testosterone to 28GST could influence the orientation of the specific immune response according to the FIG.…”
Section: Vol 70 2002mentioning
confidence: 97%